Intangible staff motivation - Shilo, A. S. (ТДАТУ, 2019)
Each manager himself chooses the intangible modern methods of motivation of the organization’s personnel, that are appropriate for his business, will help to achieve maximum returns from employees.
Keywords: motivation; personnel; intangible motivation